An introduction to theories of personality - Hergenhahn, B. R., 1934-; Olson, Matthew H. (Upper Saddle River : Prentice Hall, 2003)
For Sophomore/Junior-level courses in Theories of Personality, Personality, Individual Differences. Using a theorist-by-theorist approach, this widely-adopted introduction to theories of personality summarizes the major theories and emphasizes that the best understanding of personality derives from a variety of viewpoints. This comprehensive, unbiased approachtogether with student-tested experiential exercisesnot only introduces students to the rich history of psychology but to practical information that helps them understand their own lives and their relationships with other people.
This introduction to the theories of personality introduces readers not only to the rich history of psychology but topracticalinformation that helps them understand their own lives and their relationships with other people. Using a theorist-by-theorist approach, the book summarizes the major theories of personality and emphasizes that the best understanding of personality derives from avarietyof viewpoints. Thus, theories representing the psychoanalytic, sociocultural, trait, learning, sociological, and existential-humanistic paradigms are offered as differentyet equally validways of approaching the study of personality. Includes a series of experiential exercises.What Is Personality' Sigmund Freud. Carl Jung. Alfred Adler. Karen Horney. Erik H. Erikson. Gordon Allport. Raymond B. Cattell and Hans J. Eysenck. B. F. Skinner. John Dollard and Neal Miller. Albert Bandura and Walter Mischel. Edward O. Wilson. George Kelly. Carl Rogers. Abraham Maslow. Rollo Reese May.For anyone wanting a comprehensive understanding of personality and individual differences.
What Is Personality? -- Sigmund Freud -- Carl Jung -- Alfred Adler -- Karen Horney -- Erik H. Erikson -- Gordon Allport -- Raymond B. Cattell and Hans J. Eysenck -- B. F. Skinner -- John Dollard and Neal Miller -- Albert Bandura and Walter Mischel -- Edward D. Wilson -- George Kelly -- Carl Rogers -- Abraham Maslow.
Includes bibliographical references (p. 569-614) and indexes.
1
Keywords: Personality -- History -- Textbooks